Prediction of Waste Heat Energy Recovery Performance in a Naturally Aspirated Engine Using Artificial Neural Network - Putra, Azma; Safarudin Gazali , Herawan; Abdul Hakim, Rohhaizan; Ahmad Faris , Ismail (Hindawi Publishing Corporation, 2014)
he waste heat from exhaust gases represents a signiicant amount of thermal energy, which has conventionally been used for combined heating and power applications. his paper explores the performance of a naturally aspirated spark ignition engine equipped with waste heat recovery mechanism (WHRM).he experimental and simulation test results suggest that the concept is thermodynamically feasible and could signiicantly enhance the system performance depending on the load applied to the engine. he simulation method is created using an artiicial neural network (ANN) which predicts the power produced from theWHRM.